Assessment of hydromorphological conditions of the river using the MQI method (Case study area: JAJROOD River) - Maryam Ilanloo; Amir Karam (تحقیقات کاربردی علوم جغرافیایی)
The destruction of the rivers and, consequently, the need to reconstruct them, is one of the known important problems in throughout the world. However, suitable methods for assessing the morphological changes (morphology) associated with this action, as well as the cognition of the effect of the morphological factors in order to intervention in the process of river reconstruction, are still being explored. The JAJROOD and LATYAN-dam areas in the north east of Tehran due to the pleasant weather have always been and are in Eco tourists and nature interested people noteworthy. For this reason, during the recent decades and because of human manipulations, the JAJROOD River basin and its margins have been heavily affected. Hence the study of hydro morphological changes in this river is strongly needed. The object of this research is to evaluate the hydro morphological conditions of one part of JAJROOD River using the MQI method. Accordingly, Landsat 8 satellite images of 2018 and Landsat 4 in 1976 were prepared and were take placed several field observations. The results of the research show that all areas of the region are in poor and very weak conditions regarded to the MQI method. These problems are caused by the cutting of trees in order to create human structures, harvesting sand, creating numerous promenades along the river's estuaries and changing the river pattern.